Envejecimiento y derechos humanos - Miranda Bonilla, Haideer (2021)
The present study aging as a human rights issue that involves not only the recognition of rights and obligations for States and society, but also respect for the autonomy and independence of older people. In addition, the level of protection that older people have received at the regulatory level is studied, at the constitutional, conventional and supranational levels, which evidences the existence of legal or multilevel pluralism.